Clinical efficacy and tolerability of 1.5 g/day oral amoxicillin therapy without probenecid for the treatment of syphilis. (29th March 2021) - Ikeuchi, Kazuhiko; Fukushima, Kazuaki; Tanaka, Masaru; Yajima, Keishiro; Imamura, Akifumi
Abstract : Objectives: Intramuscular benzathine penicillin G is not available in certain countries. In a previous report, 3 g/day amoxicillin with probenecid was shown to be effective in treating syphilis in patients with HIV; however, 7.3% of patients changed their therapy owing to adverse events. The objective of this study was to assess the clinical efficacy and tolerability of 1.5 g/day amoxicillin without probenecid for the treatment of syphilis. Methods: The routine clinical records of patients diagnosed with syphilis and treated with 1.5 g/day amoxicillin at a tertiary care hospital between 2006 and 2018 were retrospectively analysed. Syphilis was diagnosed if serum rapid plasma reagin (RPR) titres were ≥8 RU and the Treponema pallidum latex-agglutination test was positive. Serological cure was defined as a ≥fourfold decrease in the RPR titre within 12 months in symptomatic early syphilis and within 24 months in latent syphilis. Results: Overall, 138 patients (112 with HIV) were analysed. The percentages of primary, secondary, early latent, late latent and latent syphilis of unknown duration were 8.0%, 50.0%, 25.4%, 5.8% and 10.9%, respectively. The median treatment duration was 4.5 weeks (IQR 4–8 weeks), which was not related to the stage of syphilis. Two patients (1.5%) changed treatment due to skin rash. The rate of serological cure was 94.9% (131/138; 95% CI 89.8% to 97.9%) overall; 93.8% (105/112; 95% CI 87.5% to 97.5%) in patients with HIV and 100% (26/26; 95% CI 86.8% to 100%) in patients without HIV. Treatment duration was not related to the treatment efficacy. Conclusion: The regimen of 1.5 g/day amoxicillin without probenecid is highly effective with a low switch rate in patients with and without HIV.